Characterization of Glycosylation-Specific Systemic and Mucosal IgA Antibody Responses to Escherichia coli Mucinase YghJ (SslE) - Riaz, Saman; Steinsland, Hans; Thorsing, Mette; Andersen, Ann Z.; Boysen, Anders; Hanevik, Kurt (Frontiers in Immunology, 2021)
Efforts to develop broadly protective vaccines against pathogenic Escherichia coli are ongoing. A potential antigen candidate for vaccine development is the metalloprotease YghJ, or SslE. YghJ is a conserved mucinase that is immunogenic, heavily glycosylated, and produced by most pathogenic E. coli. To develop efficacious YghJ-based vaccines, there is a need to investigate to what extent potentially protective antibody responses target glycosylated epitopes in YghJ and to describe variations in the quality of YghJ glycosylation in the E. coli population. In this study, we estimated the proportion of anti-YghJ IgA antibodies that targeted glycosylated epitopes in serum and intestinal lavage samples from 21 volunteers experimentally infected with wild-type enterotoxigenic E. coli (ETEC) strain TW10722. By using a multiplex bead flow cytometric assay based on glycosylated and non-glycosylated YghJ, and by analyzing samples from before and 10 days after TW10722 was ingested, we found that 20 (95%) of the 21 volunteers had IgA antibody responses to homologous, glycosylated YghJ, with a median fold increase in IgA levels of 7.9 (interquartile range [IQR]: 7.1, 11.1) in serum and 3.7 (IQR: 2.1, 10.7) in lavage. The median proportion of anti-YghJ IgA response that specifically targeted glycosylated epitopes was 0.45 (IQR: 0.30, 0.59) in serum and 0.07 (IQR: 0.01, 0.22) in lavage. By performing BEMAP analyses, we found that the glycosylation pattern of YghJ from TW10722 partially overlapped with that of ETEC reference strain H10407. Our findings suggest that a substantial, but variable, proportion of the IgA antibody response to YghJ in serum during ETEC infection is targeted against glycosylated epitopes, but that gut IgA responses largely target non-glycosylated epitopes. Further research into IgA targeting glycosylated YghJ epitopes is of interest to the vaccine development efforts.